Korespondensi antara Faktor Ketidaknyamanan Lingkungan Kerja dengan Keinginan untuk Pindah Ruang - Fildza Zatalini Zakirah; Hafshah Salamah; Hanson Endra Kusuma (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
The work environment has a great influence on motivation, performance and individual willingness to stay in their workspace. It will affect individual intention to move to a better place according to them. This study aims to determine the relationship between discomfort factors on the working environment with the intention to move from a workspace based on the individual indoor worker perception. This study uses qualitative methods and a grounded theory approach with non-random sampling and online questionnaires for data collection. The results revealed that there were five main categories of discomfort in the workspace, that is thermal discomfort, poor interior design, unsupported working atmosphere, inadequate indoor facilities, and poor indoor lighting intensity. Among those five categories, thermal discomfort has become the thing that most influences an individual's desire to move from their workspace. It can be concluded that there are three groups of factors that represent work inconvenience, namely: factors that are very influential, tend to be influential and have less effect on individual inconvenience to their work environment